(untitled) (Research, Society and Development, 2022)
Objective: The aim of this observational study was to evaluate the effectiveness of the complete digital workflow in the manufacture of implant-supported screw-retained prostheses regarding to their passive fitting. Materials and Methods: This study presents a preliminary result, part of the project approved by the Ethics Committee of Centro Universitário José Campos Andrade (UNIANDRADE) under number 3,367,320. The sample consisted of 9 patients who had partially edentulous areas with 2 to 3 healed implants, selected at clinic of Faculdade Ilapeo according to the inclusion criteria. All were rehabilitated with metal ceramics multiple implant-supported screw-retained partial dentures. The abutments were selected according to the characteristics of the peri-implant tissues. The frameworks were milled in cobalt-chrome and veneered. The passive fitting of infrastructure was used as a criterion for evaluating the effectiveness of the complete digital workflow through the Sheffield Test criteria. Printed models were used to apply the veneering ceramics. Results: This preliminary result presents 14 implant-supported screw-type fixed prostheses, installed in nine patients. All infrastructures showed a positive result according to the evaluation criteria. Conclusions: Based on the preliminary results presented, it seems fair to conclude that the complete digital workflow shows the necessary effectiveness for obtaining metal ceramic multiple implant-supported screw-retained partial dentures, as a prevalence of prostheses that presented passive sfitting was observed.